Mobility Indices in Continuous Time Markov Chains - Geweke, John; Marshall, Robert C.; Zarkin, Gary A. (Econometrica, 1986)
[The axiomatic derivation of mobility indices for first-order Markov chain models in discrete time is extended to continuous-time models. Many of the logical inconsistencies among axioms noted in the literature for the discrete time models do not arise for continuous time models. It is shown how mobility indices in continuous time Markov chains may be estimated from observations at two points in time. Specific attention is given to the case in which the states are fractiles, and an empirical example is presented.]